Innovating for the Future: A Bibliometric Examination of Business Strategy Research and the Pursuit of Market Leadership - Mardiah, Ainil; Ramadhi, Ramadhi; Santy Sriharyati; Erwina Kartika Devi (Eastasouth Institute, 2023)
This research conducts a comprehensive bibliometric analysis of the literature on business strategy and the pursuit of market leadership. By employing bibliometric techniques and leveraging the VOSviewer software, the study identifies key authors, journals, keywords, and citation patterns within the field. The analysis reveals influential contributors, emerging trends, and interconnected themes that have shaped strategic thinking. The study offers valuable insights for scholars, practitioners, and policymakers seeking to understand the dynamics of business strategy and its implications for achieving market leadership. By examining the evolution of research, the research methodology, results, and discussions, this research aims to contribute to informed decision-making and future research directions in the pursuit of market leadership.